2016
DOI: 10.1242/jcs.196725
|View full text |Cite
|
Sign up to set email alerts
|

JAK/STAT signalling mediates cell survival in response to tissue stress

Abstract: Tissue homeostasis relies on the ability of tissues to respond to stress. Tissue regeneration and tumour models in Drosophila have shown that c-Jun amino-terminal kinase (JNK) acts as a prominent stress-response pathway promoting injury-induced apoptosis and compensatory proliferation. A central question remaining unanswered is how both responses are balanced by activation of a single pathway. Signalling through the Janus kinase/Signal transducers and activators of transcription (JAK/STAT) pathway, which is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…5E-F, Additional file S3). Genes upregulated in ZWf embryos compared to ZZf embryos included STAT1 , a component of the JAK-STAT pathway, with several roles in stress responses (62), and MAP3K1 and MAPK8 , which are typically involved in mediating stress-related signal transduction cascades (6365). TERF2IP is also upregulated; this gene is involved in telomere length maintenance and transcription regulation (66).…”
Section: Resultsmentioning
confidence: 99%
“…5E-F, Additional file S3). Genes upregulated in ZWf embryos compared to ZZf embryos included STAT1 , a component of the JAK-STAT pathway, with several roles in stress responses (62), and MAP3K1 and MAPK8 , which are typically involved in mediating stress-related signal transduction cascades (6365). TERF2IP is also upregulated; this gene is involved in telomere length maintenance and transcription regulation (66).…”
Section: Resultsmentioning
confidence: 99%
“…50,132 The JNK component fos and the proapoptotic gene hid are regulated in a JAK/STAT-dependent manner. 133 The microvesicles, which induce the proliferation of neighboring cells, and this process requires JNK activity. 136 The mTOR pathway mediates beta cell compensatory proliferation in mice with a partial (60%) pancreatectomy, indicating that autophagy may be involved in this process.…”
Section: Compensatory Cell Proliferation Promotes Jnk-mediated Cancmentioning
confidence: 99%
“…However, we cannot exclude the possibility that other mechanisms might be more important. A previous study has shown that reducing JAK/STAT signaling reduced tissue loss following egr-induced ablation, but did not seem to compromise the extent of compensatory proliferation (La Fortezza et al, 2016).…”
Section: Identifying Manipulations To Promote Regeneration In Mature mentioning
confidence: 87%
“…The 1458 genes that are closest to the 729 MS peaks represent 1143 unique genes, with individual genes being associated with 1-8 peaks ( Supplemental table 6). In addition to the Wnt pathway, the JAK/STAT pathway (Katsuyama et al, 2015;La Fortezza et al, 2016) and the Hippo pathway (Grusche et al, 2011;Sun and Irvine, 2011) have been shown to be required for regeneration in imaginal discs. Moreover, we have previously shown that the activity of each of these two pathways is markedly different in early and late L3 discs following damage (Harris et al, 2016).…”
Section: Mmp1mentioning
confidence: 99%